Impact of local electrostatic field rearrangement on field ionization - Katnagallu, S; Dagan, M; Parviainen, S; Nematollahi, A; Grabowski, B; Bagot, P; Rolland, N; Neugebauer, J; Raabe, D; Vurpillot, F; Moody, M; Gault, B (IOP Publishing, 2018)
© 2018 IOP Publishing Ltd. Field ion microscopy allows for direct imaging of surfaces with true atomic resolution. The high charge density distribution on the surface generates an intense electric field that can induce ionization of gas atoms. We investigate the dynamic nature of the charge and the consequent electrostatic field redistribution following the departure of atoms initially constituting the surface in the form of an ion, a process known as field evaporation. We report on a new algorithm for image processing and tracking of individual atoms on the specimen surface enabling quantitative assessment of shifts in the imaged atomic positions. By combining experimental investigations with molecular dynamics simulations, which include the full electric charge, we confirm that change is directly associated with the rearrangement of the electrostatic field that modifies the imaging gas ionization zone. We derive important considerations for future developments of data reconstruction in 3D field ion microscopy, in particular for precise quantification of lattice strains and characterization of crystalline defects at the atomic scale.